(untitled) (Research, Society and Development, 2022)
Sensory analysis, by interpreting and measuring reactions to food characteristics, helps in evaluating the perception of products and their possible acceptance by the consumer market. This article is the result of a case study regarding the perspective of the employees of a dairy about the new formulation of cream cheese. Sensory analysis was performed with 30 untrained evaluators, using acceptance tests by a nine-point hedonic scale for texture, flavor, appearance, and aroma attributes and purchase intention through a five-point hedonic scale. In addition, a form consisting of seven multiple-choice questions was applied, referring to sex, age, education level, income, frequency of consuming the product, how it consumes, which attributes make you like cream cheese, and finally, which attributes the consumer usually analyzes in a product at the time of purchase, to better understand the profile of potential consumers. The data analysis used was descriptive statistics, performed using Excel 2013 software. The product had excellent acceptance of sensory attributes and more than 80% of the panelists would certainly buy the product. It was concluded in this study that the reformulation of cream cheese is feasible and it was identified that a potential consumer profile can be women, aged between 22 and 40 years, with higher education and income of two to four minimum wages.